(3OhGA OGA GdbdhH heYQaI gee GdfaSs - (3CMeO Hf YGUe GdGfWGcjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ceG gh Cgdg hceG jfHZj dcQe hLgg hUdi Gddg Ydi eMeO GdfHj hYdi Bdg hSde cKjQoG QMe Gddg YHOkG Yfi HfaSg HGdfXQ dgG s
(3BNQgG (B:s
(3hEfeG bGd Pdc ThGP ef GdfGS djShG HCFeI jbJOG Hge hajeG PcQfGg ef OdGFd GdcJGH hCbGhjd GdCFeI caGjI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI aj HjQhJ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs